Economic evaluation of occupational therapy in Parkinson's disease: A randomized controlled trial. Issue 8 (8th April 2015) - Sturkenboom, Ingrid H.W.M.; Hendriks, Jan C.M.; Graff, Maud J.L.; Adang, Eddy M.M.; Munneke, Marten; Nijhuis‐van der Sanden, Maria W.G.; Bloem, Bastiaan R.
Abstract Background A large randomized clinical trial (the Occupational Therapy in Parkinson's Disease [OTiP] study) recently demonstrated that home‐based occupational therapy improves perceived performance in daily activities of people with Parkinson's disease (PD). The aim of the current study was to evaluate the cost‐effectiveness of this intervention. Methods We performed an economic evaluation over a 6‐month period for both arms of the OTiP study. Participants were 191 community‐dwelling PD patients and 180 primary caregivers. The intervention group (n = 124 patients) received 10 weeks of home‐based occupational therapy; the control group (n = 67 patients) received usual care (no occupational therapy). Costs were assessed from a societal perspective including healthcare use, absence from work, informal care, and intervention costs. Health utilities were evaluated using EuroQol‐5d. We estimated cost differences and cost utility using linear mixed models and presented the net monetary benefit at different values for willingness to pay per quality‐adjusted life‐year gained. Results In our primary analysis, we excluded informal care hours because of substantial missing data for this item. The estimated mean total costs for the intervention group compared with controls were €125 lower for patients, €29 lower for caregivers, and €122 higher for patient–caregiver pairs (differences not significant). At a value of €40, 000 per quality‐adjusted life‐year gained (reported threshold for PD), the net monetary benefit of the intervention per patient was €305 (P = 0.74), per caregiver €866 (P = 0.01) and per patient–caregiver pair €845 (P = 0.24). Conclusion In conclusion, occupational therapy did not significantly impact on total costs compared with usual care. Positive cost‐effectiveness of the intervention was only significant for caregivers. © 2015 International Parkinson and Movement Disorder Society